Military production in Russian official statistics of industrial output - Julian Cooper (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2025)
This paper examines the growth of military production in Russia since the onset of the war against Ukraine in February 2022. Utilizing official data from Rosstat, the study explores how military production is classified within Russian industrial output statistics. The analysis reveals significant increases in the production of military goods, particularly in the machine building and chemical industries, despite the impact of Western sanctions. The paper highlights the complexities of isolating military production due to the inclusion of civilian goods produced by defense companies. The findings suggest that while sanctions have affected the types and modernity of military goods, they have not significantly hindered Russia's ability to produce these goods in large quantities. The study concludes that the Russian economy has been militarized to a partial extent, supporting the view that it is not a full-scale war economy but one adapted to conducting a war.
urn:nbn:fi-fe2025031718238
Keywords: 330; Russia; economy; war; sanctions